“I think that poets and, more broadly, all artists have some certain cognitive impatience in them”: An Interview with Professor Jerzy Kandziora about Stanisław Barańczak, Conducted by Karolina Król - Król, Karolina; Kandziora, Jerzy (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
The interview covers the subject of Stanisław Barańczak and his works. Pondering on the way the poet pictures the existence of God in his poems is an important part of the text. Another crucial subject is the way Barańczak deals with his illness and portrays it in his poetic works. In the interview Jerzy Kandziora – an exquisite reasercher of the poetry written by Barańczak and Jerzy Ficowski − mentions his private relationship with both Barańczak and his wife.